2013
DOI: 10.1111/jir.12084
|View full text |Cite
|
Sign up to set email alerts
|

Influence of mobbing (workplace bullying) on depressive symptoms: a longitudinal study among employees working with people with intellectual disabilities

Abstract: We conclude that permanence of mobbing from Time 1 to Time 2 increases depressive symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 44 publications
4
37
0
2
Order By: Relevance
“…Workplace conflicts including mobbing are known to have a negative impact on health and are well known to increase the risk of depression, anxiety and sleep disorders [6], [7], [8]. By contrast, few studies have focused on the association between workplace mobbing and negative cardiovascular outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Workplace conflicts including mobbing are known to have a negative impact on health and are well known to increase the risk of depression, anxiety and sleep disorders [6], [7], [8]. By contrast, few studies have focused on the association between workplace mobbing and negative cardiovascular outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Despite some geographical preferences, mobbing, bullying, and harassment are interchangeable terms [4]. Workplace mobbing is known to have a negative impact on health [5] and mobbing at work has been significantly associated with depression, anxiety, and sleep disorders [6], [7], [8]. …”
Section: Introductionmentioning
confidence: 99%
“…Más recientemente, Gil-Monte, Carretero y Luciano (2006) crearon un nuevo cuestionario denominado Mobbing-UNIPSICO Scale, + que es una adaptación de 20 ítems provenientes tanto del LIPT como del NAQ, y ha sido utilizado para evaluar a empleados que trabajan con personas con discapacidad intelectual (Figueiredo-Ferraz, Gil-Monte, Grau-Alberola, Llorca-Pellicer, & García-Juesas, 2012;Figueiredo-Ferraz, Gil-Monte, & Olivares-Faúndez, 2015). Así mismo, estudios como el de León-Pérez, Notelaers, Arenas, Munduate y Medina (2014) han abordado el estudio del acoso laboral desde una perspectiva metodológica distinta a la anteriormente señalada, la cual se enfoca en la descripción de perfiles de acoso.…”
Section: Medición Del Acoso Psicológico En El Trabajounclassified
“…1 Previous studies have shown an association between bullying, measured either as exposure to negative acts or as self-labeled bullying, and mental health problems, 2,3 as well as a lowered diurnal level of salivary cortisol as an indicator of physiological stress response. 4,5 Furthermore, some longitudinal studies have found self-labeled bullying to be a predictor of psychological distress, 6,7 depressive symptoms, 8,9 and depression. 10 Depression is characterized by depressive mood, loss of interest, and decreased energy accompanied by additional symptoms such as loss of self-esteem.…”
mentioning
confidence: 97%